Assessment of psychological traits in medalists and non-medalists junior Indian boxers - Malik, P. (International Journal of Physiology, Nutrition and Physical Education, 2019)
The purpose of the present study was to assess the psychological traits in medalists and non-medalist junior Indian boxers. A total of (N=60); 16 medalists and 44 non-medalists Junior Indian Boxers with age ranging between 15 -20 years were selected as subjects for a comparative study. Psychological variables selected for the present study were aggression, motivation and trait and state anxiety. Motivation was measured by questionnaire constructed by Dr.M.L.Kamlesh (1992), anxiety i.e. trait and state anxiety were measured by the questionnaire constructed by Dr. Speilberger, (1966). To measure the aggression questionnaire developed by Buss & Perry (1992) was used. Independent T-Test was employed for the analysis of data and the levelof significance was set at 0.05. The results indicated that Concentration (P=0.05) and Self Confidence (P= 0.00) have a significant difference between the Medalist and non-medalists boxers. All other variables found insignificant.